2013
DOI: 10.1080/17457300.2013.833941
|View full text |Cite
|
Sign up to set email alerts
|

The rate of seat belt use and its related factors among car drivers in Tehran, Iran after imposing new regulations

Abstract: The incidence of road crash deaths is high in Iran. Seat belts can reduce the risk of death or serious injury. This study aimed to estimate the rate of seat belt use and its related factors for car drivers in Tehran, Iran after proclamation of the 2011 legislation. A roadside observational study was conducted in 2012 and 10,752 cars and taxis commuting in different streets of Tehran were screened in regard to drivers' seat belt wearing. Other variables including gender, age range, type of street, district, tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In our study, we investigated the rate of seat belt usage in traumatically injured car occupants and concluded that 68% of them used this safety device. Seat belt enforcement by police and law fines could lead to increase the use of seat belts in our study and Nabipour et al with 70.9% ( 14 ) compared with Borghebani et al study that 53% of drivers were fasten seat belts at 2009 ( 12 ). Similar to Abu-Zidan et al study ( 8 ) the unbelted patients were significantly younger than the belted ones.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In our study, we investigated the rate of seat belt usage in traumatically injured car occupants and concluded that 68% of them used this safety device. Seat belt enforcement by police and law fines could lead to increase the use of seat belts in our study and Nabipour et al with 70.9% ( 14 ) compared with Borghebani et al study that 53% of drivers were fasten seat belts at 2009 ( 12 ). Similar to Abu-Zidan et al study ( 8 ) the unbelted patients were significantly younger than the belted ones.…”
Section: Discussionsupporting
confidence: 54%
“…Women, regardless of their occupant position, used seat belts significantly more than men in our study. Nabipour et al study in Iran 2013 reports the rate of the seat belt usage was significantly higher in female drivers ( 14 ). Afukaar et al study in Ghana 2010 ( 16 ), Ipingbemi et al study in Nigeria 2012 ( 6 ) and Ma et al study in Russia 2012 ( 17 ) also report this finding in female drivers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study in Tehran (capital city of Iran) reported a seatbelt wearing rate of 70.9% among car drivers (27). However, this rate was reported to be 90% for all Iranian drivers in 2010 (1).…”
Section: Discussionmentioning
confidence: 99%
“…As a medium-income country, Iran has a high RTC injury and mortality rate (Bendak, 2005, Kononen et al, 2011. In 2010 RTCs accounted for a total of 414,161 injuries and 23,249 fatalities in Iran (Bahadorimonfared et al, 2013). This translates into a rate of 34.1 per 100,000 people, which is the fourth highest rate in the world, after the Dominican Republic (41.7/100,000), Thailand (38.1/100,000) and Venezuela (37.2/100,000).…”
Section: Introductionmentioning
confidence: 99%